Hypersensitivity reactions to food and drug additives: problem or myth? - Andreozzi, Laura; Giannetti, Arianna; Cipriani, Francesca; Caffarelli, Carlo; Mastrorilli, Carla; Ricci, Giampaolo (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: The possibility of an allergic reaction or an intolerance to additives is frequently suspected by parents, especially for chronic illness with frequent exacerbations such as atopic dermatitis or chronic urticaria. For more than 50 years, potential adverse reactions to additives have been suggested, but to date data are conflicting. The purpose of this article is to provide the clinicians with general information about additives and adverse reactions to them and to suggest a practical approach to children suspected to have reactions to food additives. Methods: We performed an extensive research on all English-language Medline articles, case reports and reviews published online until December 2018. Used search terms were: food additives, food dye, adverse reactions, food allergy, food hypersensitivity, intolerance, drugs, children. Results: There are only few case reports of adverse reactions in childhood with a clear involvement of additives. In this review article we reported the associations between additives and adverse reactions described in literature, in order to inform the pediatrician about the potential clinical manifestations. Conclusions: Prior to suspect an adverse reaction to additives, it is important to rule out other possible causes: the diagnostic process is complicated and rarely conclusive. The gold standard is the double-blind placebo controlled oral challenge after an exclusion diet.